Rare bird documentation form for Northern Goshawk at Green Castle Corner in Johnson County, 1982 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1982)
Rare bird documentation form for two Northern Goshawks at Green Castle Corner in Johnson County, IA on October 31, 1982. Epson - sheet feed